Legal Analysis of the Application of Criminal Sanctions Against Perpetrators of Aggravated Theft Based on Pancasila Justice (Criminal Case Study Decision Number: 170/Pid.B/2024/PN.Skt) - Sutadharma, Putu Andy; Bawono, Bambang Tri (UNISSULA Semarang, 2025)
The background of the problem began with the rampant corruption cases in the Village Credit Institutions (LPD) in Bali. LPD management that deviates from the provisions of laws and regulations is prosecuted as a criminal act of corruption. The dilemma in imposing a replacement fine on LPD corruption cases in Bali is interesting to study further. If the replacement money is paid to the State Treasury, the state's loss in this case the LPD's loss is irrecoverable. Several judges' decisions impose a replacement fine with the order that reads